Kaplan–Meier Survival Analysis of Breast Cancer Patients by Estrogen Receptor Status - Ayu Rahayu (ARRUS Journal of Mathematics and Applied Science, 2026)
Breast cancer is one of the leading causes of death among women worldwide, making survival analysis essential in evaluating patient survival probabilities. This study aims to estimate the survival function of breast cancer patients based on Estrogen Receptor Status using the nonparametric Kaplan-Meier estimator. Secondary data from the Breast Cancer Survival dataset on Kaggle (n = 4,024 patients) were analyzed. Variables included survival time (Survival Months), event status (Status), and Estrogen Receptor Status (Positive/Negative). Results showed that patients with Estrogen Receptor-Positive status exhibited a higher survival probability compared to Estrogen Receptor-Negative patients, as indicated by the slower decline of their Kaplan-Meier survival curve. These findings confirm that estrogen receptor status is an important prognostic factor in breast cancer and that the Kaplan-Meier estimator provides an effective nonparametric approach to evaluating patient survival